Assessing Human Reproductive Cloning and Creationism from the Perspectives of Raelianism and African Belief - Ottuh, Peter (Jurnal Office, 2020)
This paper appraised the issues involved in human reproductive cloning and creationism from the standpoints of Raelian religion and African traditional belief. The methods adopted are descriptive and evaluative. The findings include the fact that human cloning is one of the religious tenets of Raelianism; and that African tradition and culture totally reject reproductive cloning on the ground of its unnaturalness. Finally, the paper from the African traditional paradigm concluded that human reproductive cloning is totally condemnable and should not be practiced on human beings on the ground of unnaturalness, distortion, negation, imperfection, and aberration.